Oxford new syllabus primary Mathematics book 2 - Yee, Dr foong pui (Karachi : Oxford university press, 2019)
The Oxford New Syllabus Primary Mathematics Book 2 is a mathematics textbook for primary school students, typically in the second year of their schooling. It continues to build on the foundation established in Book 1, focusing on developing students' mathematical skills and understanding of key concepts, while introducing new topics in line with the curriculum.
Keywords: Mathematics : Textbook